Sintered body and parts containing same
Patent Information
- Application Number
- JP2023120907
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-27
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2043-07-25
AI Technical Summary
【0020】 具現例に係る焼結体は、粗大結晶粒による線欠陥が減少して、プラズマエッチング時に不純物パーティクルの発生を低減させることができ、優れたプラズマ耐エッチング性を有することができ、プラズマ耐エッチング性を安定的に維持することができる。
Smart Images

Figure 0007638335000006 
Figure 0007638335000007 
Figure 0007638335000008
Abstract
Description
[Technical field]
[0001] Embodiments relate to a sintered body having improved plasma etching resistance and a part of a plasma processing apparatus including the same. [Background technology]
[0002] A plasma processing apparatus has an upper electrode and a lower electrode arranged inside a chamber, a semiconductor wafer, a glass substrate, etc., placed on the lower electrode, and operates by applying power between the two electrodes. Electrons accelerated by the electric field between the upper electrode and the lower electrode, electrons emitted from the electrodes, or heated electrons ionize and collide with molecules of the processing gas to generate plasma of the processing gas. Active species such as radicals and ions in this plasma can realize the desired microfabrication of the surface of the etching target, for example, etching processing.
[0003] As manufacturing designs for microelectronic devices become increasingly finer, higher dimensional accuracy is required, especially in plasma etching, and significantly higher power is used. Such plasma processing equipment has a built-in focus ring that is affected by the plasma.
[0004] When the plasma power becomes high, a wavelength effect in which a standing wave is formed, a skin effect in which the electric field is concentrated in the center of the electrode surface, etc. may be formed, and as a result, the plasma distribution is generally maximized in the center of the etching target and is lowest at the edge, which may cause the plasma distribution on the substrate to become significantly non-uniform, and may result in a deterioration in the quality of the microelectronic device.
[0005] The focus ring, which places the etching target on the outer periphery of the etching target, can affect the electric field distribution of the outer periphery, thereby alleviating non-uniformity of plasma distribution to some extent. However, the etching rate of the focus ring is relatively high compared to the plasma processing time, and the etching can affect the plasma distribution. There is a need for an improvement that can improve the etching resistance and replacement cycle of the focus ring and achieve process efficiency.
[0006] Related prior art includes the "boron carbide material" disclosed in Korean Patent Registration No. 10-2262340 and the "boron carbide sintered body and etching apparatus including the same" disclosed in Korean Patent Publication No. 10-2020-0019068. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the embodiment is to provide a sintered body and a part including the same that can induce uniform plasma distribution to an etching target and have improved plasma etching resistance. [Means for solving the problem]
[0008] In order to achieve the above object, the sintered body according to the embodiment is Contains boron carbide, When observed on the surface, the volume ratio of crystal grains with a crystal grain size of more than 30 μm and not exceeding 60 μm to the total crystal grains is 50% to 70%, The carbon content based on the total weight may be 30% to 43% by weight as determined by X-ray fluorescence analysis.
[0009] In an embodiment, the volume ratio of crystal grains having a crystal grain size of 10 μm or less to the total crystal grains may be 0.01% to 1%.
[0010] In an embodiment, the volume ratio of crystal grains having a crystal grain size of more than 60 μm and not more than 80 μm to the total crystal grains may be 12% to 20%.
[0011] In one embodiment, the average grain size may be 30 μm to 70 μm.
[0012] In one embodiment, the boron and carbon content may be greater than or equal to 97% by weight.
[0013] In one embodiment, under plasma etching conditions in which the chamber pressure is 100 mTorr, the plasma power is 800 W, the exposure time is 300 minutes, and the flow rates of CF4 gas, Ar gas, and O2 gas in the chamber are 50 sccm, 100 sccm, and 20 sccm, respectively, the etching rate according to the following formula 1 may be 1.8% or less.
[0014] [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%
[0015] In one embodiment, the thermal conductivity at 25° C. may be 23 W / mK or more and 42 W / mK or less.
[0016] In order to achieve the above object, a method for producing a sintered body according to an embodiment includes the steps of: a carbonization step of heat-treating a compact obtained by molding the raw material composition at a temperature of 500°C to 1000°C; After the carbonization step, a first sintering step of heat treating at a temperature of 2100°C to 2300°C; After the first sintering step, a second sintering step of heat treating at a temperature of 2200°C to 2320°C is included, The raw material composition may include boron carbide, a carbon-based material, and a sintering property improver.
[0017] In one embodiment, the raw material composition is The raw material granules may be obtained by spray drying a raw material slurry containing boron carbide, a carbon-based material, a sintering property improver, and a solvent.
[0018] In one embodiment, the first sintering step and the second sintering step are performed at a pressure of 0.2 MPa or less; The first sintering step is carried out for 0.5 to 2 hours, The second sintering step may be carried out for 1 hour to 3 hours.
[0019] In order to achieve the above object, the part according to the embodiment includes: The sintered body includes The present invention may be applied to the inside of a plasma processing apparatus. Effect of the Invention
[0020] The sintered body according to the embodiment may have fewer line defects due to coarse crystal grains, thereby reducing the generation of impurity particles during plasma etching, and may have excellent plasma etching resistance and stably maintain the plasma etching resistance. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1(a) is a scanning electron microscope photograph showing the surface of the sintered body of Example 1 before electrolytic etching in the experimental example, FIG. 1(b) is a scanning electron microscope photograph showing the surface of the sintered body of Example 1 after electrolytic etching in the experimental example, and FIG. 1(c) is a diagram showing identifiable crystal grains differentiated by color in the scanning electron microscope photograph of the surface of the sintered body of Example 1 after electrolytic etching in the experimental example. [Diagram 2] 1(a) is a photograph showing the state of the sample of Example 1 after plasma etching in the experimental example, and (b) is a photograph showing the state of the sample of Comparative Example 1 after plasma etching in the experimental example. [Diagram 3] FIG. 1(a) is a diagram showing the surface of the sintered body of Example 1 and the measurement positions of the composition before electrolytic etching, and FIG. 1(b) is a diagram showing the surface of the sintered body of Example 1 and the measurement positions of the composition after electrolytic etching. [Figure 4] FIG. 1(a) is a diagram showing the surface state of Example 1 before plasma etching, and FIG. 1(b) is a diagram showing the surface state of Example 1 after plasma etching. [Diagram 5] FIG. 1(a) is a diagram showing the surface state of Comparative Example 1 before plasma etching, and FIG. 1(b) is a diagram showing the surface state of Comparative Example 1 after plasma etching. BEST MODE FOR CARRYING OUT THEINVENTION
[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS One or more exemplary embodiments will now be described in detail with reference to the accompanying drawings in order to enable those of ordinary skill in the art to easily make and use the present invention. However, the exemplary embodiments may be embodied in many different forms and are not limited to the embodiments set forth herein. Like reference numerals are used throughout the specification to refer to like parts.
[0023] In this specification, when a certain configuration "includes" another configuration, this does not mean to exclude the other configurations, unless specifically stated to the contrary, but rather means that the other configurations may also be included.
[0024] In this specification, when a certain component is said to be "connected" to another component, this includes not only the case where the component is "directly connected" but also the case where the component is "connected via another component between them."
[0025] In this specification, the term "B is located on A" means that B is located on A in direct contact therewith, or that B is located on A with another layer located therebetween, and is not to be interpreted as being limited to B being located in contact with the surface of A.
[0026] As used herein, the term "combinations thereof" contained in a Markush form expression means a mixture or combination of one or more selected from the group of components set forth in the Markush form expression, and is meant to include one or more selected from the group of components.
[0027] In this specification, the phrase "A and / or B" means "A, B, or A and B."
[0028] In this specification, terms such as "first", "second" or "A", "B" are used to distinguish identical terms from each other, unless otherwise specified.
[0029] In this specification, the term "singular" is to be construed as including the singular or plural as the context requires, unless otherwise specified.
[0030] Sintered body In order to achieve the above object, the sintered body according to the embodiment is Contains boron carbide, When observed on the surface, the volume ratio of crystal grains with a crystal grain size of more than 30 μm and not exceeding 60 μm to the total crystal grains is 50% to 70%, The carbon content based on the total weight may be 30% to 43% by weight as determined by X-ray fluorescence analysis.
[0031] The boron carbide of the sintered body may be substantially B4C.
[0032] The sintered body is based on boron carbide and contains a specific carbon separate from boron carbide, and contains some silicon, silicon carbide (Si x C y ), oxygen, boron oxide, etc. The carbon, silicon carbide, etc. of the sintered body may also be present in the form of a secondary phase.
[0033] The sintered body may include boron carbide grains, which may also be observed at the surface of the sintered body.
[0034] The sintered body may have a coarse average grain size compared to conventional boron carbide sintered bodies.
[0035] In the sintered body, the volume ratio of crystal grains having a crystal grain size of more than 30 μm and not more than 60 μm to all crystal grains may be 50% to 70%, or may be 55% to 65%.
[0036] The sintered body may have a volume ratio of crystal grains having a crystal grain size of 10 μm or less to all crystal grains of 0.01% to 1%, or 0.01% to 0.81%.
[0037] The sintered body may have a volume ratio of crystal grains having a crystal grain size of 20 μm or less to all crystal grains of 2% to 14%, or 1% to 10%.
[0038] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 60 μm and not more than 80 μm to all crystal grains of 12% to 20%, or 14% to 18%.
[0039] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 40 μm to all crystal grains of 44% to 65%, or 49% to 60%.
[0040] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 70 μm to all crystal grains of 8% to 15%, or 9.1% to 13.7%.
[0041] The sintered body may have an average crystal grain size of 30 μm to 70 μm, or 45 μm to 65 μm.
[0042] The grain size of the sintered body may be analyzed by the method described in the following Experimental Examples, and may be based on the grain size observed on the surface.
[0043] A sintered body having such crystal grain characteristics can reduce line defects, reduce the generation of impurity particles during plasma etching, and have excellent plasma etching resistance, which can be useful for maintaining plasma etching resistance.
[0044] The sintered body may have a purity of 97% or more, 99% or more, or 99.2% or more based on boron and carbon (B, C).
[0045] The purity is assessed on a weight basis by X-ray fluorescence analysis (XRF).
[0046] The sintered body may have a total carbon content of 30 wt% to 43 wt%, or 32 wt% to 40 wt% according to X-ray fluorescence analysis (XRF). Such a carbon content may indicate that carbon is added to the stoichiometric carbon content (21.72 wt%) of boron carbide (B4C). This may also be due to a partial change in the bonding relationship of boron carbide during the sintering process during manufacture, or due to the influence of a carbon-based substance added to the raw material during manufacture.
[0047] The sintered body may have a total boron content of 55% to 68% by weight, or 56% to 66% by weight, as determined by X-ray fluorescence analysis. Such a boron content may be due to the addition of additional carbon as described above, or may be the result of a carbonaceous material added to the raw material during production.
[0048] The sintered body may have an oxygen content of 0.1% by weight to 0.9% by weight, or 0.3% by weight to 0.7% by weight, based on the total weight, as determined by X-ray fluorescence analysis.
[0049] The sintered body may have a silicon content of 0.05% by weight to 0.5% by weight, or 0.1% by weight to 0.4% by weight, based on the total weight, as determined by X-ray fluorescence analysis.
[0050] The sintered body may play a positive role in densification due to the content of such other elements.
[0051] The sintered body may contain metallic impurities of 400 ppm or less, or 200 ppm or less. The metallic impurities may include sodium, aluminum, calcium, iron, nickel, and the like.
[0052] The flexural strength of the sintered body may be 365 MPa to 547 MPa, or 410 MPa to 502 MPa.
[0053] The sintered body may have a Vickers hardness of 26.1 GPa to 39.1 GPa, or 29.3 GPa to 35.9 GPa.
[0054] The sintered body may have a compressive strength of 549 MPa to 823 MPa, or may have a compressive strength of 617 MPa to 755 MPa.
[0055] The sintered body may have an elastic modulus of 308 GPa to 424 GPa, or may have an elastic modulus of 347 GPa to 424 GPa.
[0056] The sintered body may have a Poisson's ratio of 0.175 to 0.263, or 0.197 to 0.241.
[0057] The sintered body may have a thermal conductivity at 25° C. of 23 W / mK or more and 42 W / mK or less, or may be 30 W / mK to 40 W / mK.
[0058] The sintered body has a thermal expansion coefficient of 3.34 × 10 at 25°C to 400°C. -6 / K~5.02×10 -6 / K or 3.76 x 10 -6 / K~4.60×10 -6 / K may also be used.
[0059] The sintered body has a thermal expansion coefficient of 4.01×10 at 400°C to 800°C. -6 / K~6.02×10 -6 / K or 4.52 x 10 -6 / K~5.52×10 -6 / K may also be used.
[0060] The sintered body may have a resistivity of 0.05 Ωcm to 2 Ωcm, or may have a resistivity of 0.1 Ωcm to 1 Ωcm.
[0061] A sintered body having such characteristics can exhibit good reliability and durability when applied to parts of a plasma processing apparatus, and can be useful in maintaining plasma etching resistance.
[0062] The sintered body may have an etching rate of 1.8% or less according to the following formula 1 under plasma etching conditions in which the chamber pressure is 100 mTorr, the plasma power is 800 W, the plasma exposure time is 300 minutes, and the flow rates of CF4 gas, Ar gas, and O2 gas in the chamber are 50 sccm, 100 sccm, and 20 sccm, respectively.
[0063] [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%
[0064] The etching rate of the sintered body may be 1.6% or less, or may be 1.55% or less.
[0065] The sintered body has such plasma etching resistance and also has the characteristic of large crystal grains, so that generation of particles during the plasma treatment process can be suppressed to the maximum extent.
[0066] The sintered body may have an etching rate that is reduced by 20% or more, or may have an etching rate that is reduced by 30% or more, based on the plasma etching conditions, compared to the etching rate of silicon carbide formed by chemical vapor deposition (CVD).
[0067] The sintered body may have a relative density of 95% or more, or 97% or more. The relative density may be 99.9% or less. The sintered body may have excellent relative density while exhibiting a relatively coarse grain size.
[0068] parts In order to achieve the above object, the part according to the embodiment comprises: The sintered body includes It can be applied inside a plasma processing apparatus.
[0069] The part may include the sintered body on only a portion or on the entire surface that may be exposed to plasma.
[0070] The part may include the sintered body on a surface thereof, and the interior of the surface may include other ceramic materials (eg, silicon carbide, silicon, etc.).
[0071] The component may be a component capable of affecting a flow of plasma ions during a plasma etching process, and may be, for example, a focus ring, etc. The focus ring may be used as a support for supporting an edge of a wafer when the wafer is placed in a plasma processing apparatus.
[0072] By including the sintered body, the part can ensure good plasma etching resistance, reduce the frequency of part replacement, and effectively prevent the generation of particles that may negatively affect yield.
[0073] Manufacturing method of sintered body In order to achieve the above object, a method for producing a sintered body according to an embodiment includes: a carbonization step of heat-treating the molded body obtained by molding the raw material composition at a temperature of 500°C to 1000°C to obtain a molded body in which a part of the raw material is carbonized; After the carbonization step, a first sintering step of heat treating at a temperature of 2100°C to 2300°C; After the first sintering step, a second sintering step of heat treating at a temperature of 2200°C to 2320°C is included, The raw material composition may be raw material granules obtained by spray drying a raw material slurry containing boron carbide, a carbon-based material, a sintering property improver, and a solvent.
[0074] The boron carbide in the raw material composition may be in the form of a powder, and may be a powder having a purity of 98% by weight or more of boron and carbon based on the entire powder.
[0075] The carbonaceous material of the raw material composition may be a polymer resin, or may be a carbonized polymer resin, such as a phenol-based resin or a polyvinyl alcohol-based resin.
[0076] The sintering characteristic improver of the raw material composition may include boron oxide, a binder, etc., and the binder may include an acrylic resin.
[0077] The solvent of the raw material composition may include water, an alcohol-based substance, etc., and may be included in an amount of 60% to 80% by volume based on the entire raw material slurry.
[0078] The raw material slurry may be prepared through a stirring process using a ball mill or the like, and the ball mill stirring process may be carried out using polymer balls or the like for 5 to 20 hours.
[0079] The green body of the carbonization step can be obtained by injecting the raw material into a mold and applying pressure, such as cold isostatic pressing (CIP), etc. At this time, the pressure may be 100 MPa to 200 MPa.
[0080] The compact from the carbonization step may be subjected to a processing process to remove unnecessary parts.
[0081] The temperature rise to the heat treatment temperature in the first sintering step may be carried out for 10 to 15 hours.
[0082] The first sintering step may be carried out for 0.5 to 2 hours.
[0083] The temperature rise to the heat treatment temperature in the second sintering step may be carried out for 2 hours to 5 hours.
[0084] The second sintering step may be carried out for 1 hour to 3 hours.
[0085] After the second sintering step, a cooling step of cooling to room temperature may be performed, and may be performed for 10 to 15 hours.
[0086] Through the sintering step, a sintered body having relatively coarse crystal grains can be produced, and a good degree of densification can be achieved.
[0087] The sintered body obtained through the second sintering step may be subjected to additional shaping.
[0088] In the first sintering step, a predetermined heating rate may be applied until the heat treatment temperature is reached, and the heating rate may be 1°C / min to 10°C / min, or 2°C / min to 5°C / min.
[0089] In the second sintering step, a predetermined heating rate may be applied until the heat treatment temperature is reached, and the heating rate may be 0.1°C / min to 5°C / min, or 0.2°C / min to 1°C / min.
[0090] After the second sintering step, a predetermined temperature drop rate may be applied in a cooling step, and the temperature drop rate may be -10°C / min to -1°C / min, or may be -5°C / min to -2°C / min.
[0091] The first sintering step and the second sintering step may be performed at a pressure of 0.2 MPa or less, may be performed substantially at atmospheric pressure (0.101 MPa), or may be performed at a pressure of 0.05 MPa or more.
[0092] The present invention will be described in more detail with reference to the following specific examples. The following examples are merely illustrative for the purpose of aiding understanding of the present invention, and are not intended to limit the scope of the present invention.
[0093] Example 1 - Production of sintered body For a total of 100 parts by volume, 14 parts by volume of boron carbide powder from China Abrasive and 70 parts by volume of ethanol solvent were mixed, and then 100 parts by weight of the mixture of the powder and the solvent were mixed with 19.2 parts by weight of phenolic resin and 2 parts by weight of acrylic binder, and the composition was placed in a compounder and mixed using a ball mill method to prepare a raw material slurry. The raw material slurry was spray-dried through a nozzle to obtain raw material granules, which were then loaded into a mold to obtain a molded body. The molded body was heat-treated at a temperature of 800°C to perform a carbonization step. Then, the temperature was raised to 2200°C at a heating rate of 3°C / min, and then a first sintering step was performed in which the temperature was raised to 2300°C at a heating rate of 0.5°C / min, and then a second sintering step was performed in which the temperature was raised to 2300°C for 2 hours. Then, a cooling step was performed to cool to room temperature (25°C) at a rate of 3°C / min to produce a sintered body.
[0094] Comparative Example 1 - Silicon carbide produced by chemical vapor deposition Silicon carbide manufactured by chemical vapor deposition (CVD) from KNJ was prepared.
[0095] Experimental example - Analysis of crystal grains and composition through electrolytic etching of sintered body The sintered body produced in Example 1 was subjected to electrolytic etching under the conditions of 2% by volume KOH solution, flow rate 12-20sccm, 5 seconds, and voltage 40-51V, followed by ultrasonic cleaning for 20 minutes. The surface before and after electrolytic etching was photographed at 500-1000x magnification at three arbitrary surface regions using a scanning electron microscope (SEM), and the volume ratio of each crystal grain size was analyzed. The composition at some positions (A, B, C, D, E, F) before and after electrolytic etching was analyzed, and the results are shown in Fig. 1, Fig. 3, Table 1, Table 2, Table 3, etc.
[0096] JPEG0007638335000001.jpg4270
[0097] JPEG0007638335000002.jpg29115
[0098] JPEG0007638335000003.jpg29115
[0099] FIG. 1(a) shows the surface of the sintered body of Example 1 before electrolytic etching, FIG. 1(b) shows the surface of the sintered body of Example 1 after electrolytic etching, and FIG. 1(c) shows identifiable crystal grains on the surface of the sintered body of Example 1 after electrolytic etching, differentiated by color.
[0100] FIG. 3(a) shows the surface of the sintered body of Example 1 and the positions at which the composition was measured before electrolytic etching, and FIG. 3(b) shows the surface of the sintered body of Example 1 and the positions at which the composition was measured after electrolytic etching.
[0101] Referring to Table 1 and FIGS. 1(a) to 1(c), it can be seen that in the sintered body of Example 1, coarse crystal grains of several tens of μm are uniformly distributed, and there are almost no crystal grains of 10 μm or less.
[0102] Referring to Tables 2 and 3 and (a) to (c) of FIG. 3, in addition to boron carbide, silicon carbide, glass carbon, etc. can be confirmed on the surface of the sintered body of Example 1 before and after electrolytic etching.
[0103] Experimental example - X-ray fluorescence analysis (XRF) X-ray fluorescence spectroscopy (XRF) of the compositions of the sintered samples of Example 1 and Comparative Example 1 was performed using a Rigaku ZSX Primus instrument, and the results are shown in Table 4.
[0104] JPEG0007638335000004.jpg9195
[0105] Referring to Table 4, it can be seen that the sintered body of Example 1 contains approximately 60.91% by weight of boron, 38.35% by weight of carbon, and also contains some oxygen, silicon, and the like.
[0106] Experimental Example - Plasma Etching Rate Measurement The plasma etching rates of the sintered body samples of Example 1 and Comparative Example 1 were measured under the following conditions, and the results are shown in Tables 4 and 5, and in FIGS.
[0107] Plasma etching conditions Chamber pressure: 100 mTorr, plasma power: 800 W, exposure time: 300 min, CF4 gas flow rate: 50 sccm, Ar gas flow rate: 100 sccm, O2 gas flow rate: 20 sccm
[0108] FIG. 4(a) shows the surface state of Example 1 before plasma etching, and FIG. 4(b) shows the surface state of Example 1 after plasma etching.
[0109] FIG. 5(a) shows the surface state of Comparative Example 1 before plasma etching, and (b) shows the surface state of Comparative Example 1 after plasma etching.
[0110] JPEG0007638335000005.jpg52135
[0111] Referring to Table 5, it can be seen that in the case of Example 1, the plasma etching resistance is superior to that of silicon carbide produced by CVD.
[0112] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims also fall within the scope of the present invention.
Claims
1. Contains boron carbide, When observed on the surface, the volume ratio of crystal grains having a crystal grain size of more than 30 μm and not more than 60 μm to the total crystal grains is 50% to 70%; The carbon content based on the total weight is 30% to 43% by weight according to X-ray fluorescence analysis; A sintered body having a total boron content of 55% to 68% by weight as determined by X-ray fluorescence analysis.
2. 2. The sintered body according to claim 1, wherein the volume ratio of crystal grains having a crystal grain size of 10 μm or less to the total volume of crystal grains is 0.01% to 1%.
3. The sintered body according to claim 1, wherein the volume ratio of crystal grains having a crystal grain size of more than 60 μm and not more than 80 μm to the total crystal grains is 12% to 20%.
4. 2. The sintered body according to claim 1, having an average grain size of 30 μm to 70 μm.
5. 2. The sintered body according to claim 1, wherein the boron and carbon content is 97% by weight or more.
6. The chamber pressure was 100 mTorr, the plasma power was 800 W, and the exposure time was 300 minutes. 4 The gas flow rate is 50 sccm, the Ar gas flow rate is 100 sccm, and O 2 2. The sintered body according to claim 1, wherein under plasma etching conditions with a gas flow rate of 20 sccm, the etching rate according to the following formula 1 is 1.8% or less. [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%
7. 2. The sintered body according to claim 1, having a thermal conductivity at 25° C. of 23 W / mK or more and 42 W / mK or less.
8. A method for producing the sintered body according to claim 1, comprising the steps of: a carbonization step of heat-treating a compact obtained by molding the raw material composition at a temperature of 500°C to 1000°C; After the carbonization step, a first sintering step of heat treatment at a temperature of 2100°C to 2300°C; A second sintering step of heat treating the first sintering step at a temperature of 2200°C to 2320°C, The raw material composition comprises boron carbide, a carbon-based material, and a sintering property improver.
9. The raw material composition is The method according to claim 8, wherein the raw material granules are obtained by spray drying a raw material slurry containing boron carbide, a carbon-based substance, a sintering property improver and a solvent.
10. The first sintering step and the second sintering step are performed at a pressure of 0.2 MPa or less; The first sintering step is carried out for 0.5 to 2 hours; The method of claim 8, wherein the second sintering step is carried out for 1 hour to 3 hours.
Citation Information
Patent Citations
Boron carbide powder, method for manufacturing the same, and boron carbide-based compact and boron carbide-based sintered compact using the same
JP2008239471A
Ceramic powder-dispersed aluminum composite material
JP2016079465A
Boron carbide sintered body and etcher including the same
JP2020073420A
Ring-shaped element for etcher and method for etching substrate using the same
US20200051793A1
Ceramic component and plasma etching apparatus comprising same
WO2021162424A1